Linking heart rate variability to psychological health and brain structure in adolescents with and without conduct disorder - Cubillo, Ana; Tkalcec, Antonia; Oldenhof, Helena; Unternaehrer, Eva; Raschle, Nora; Kohls, Gregor; Nauta-Jansen, Lucres; Hervas, Amaia; Fernandez-Rivas, Aranzazu; Konrad, Kerstin; Popma, Arne; Freitag, Christine; et al. (Frontiers in Psychiatry, 2023)
Heart rate variability (HRV) measures have been suggested in healthy individuals as a potential index of self-regulation skills, which include both cognitive and emotion regulation aspects. Studies in patients with a range of psychiatric disorders have however mostly focused on the potential association between abnormally low HRV at rest and specifically emotion regulation difficulties. Emotion regulation deficits have been reported in patients with Conduct Disorder (CD) however, the association between these emotion regulation deficits and HRV measures has yet to be fully understood. This study investigates (i) the specificity of the association between HRV and emotion regulation skills in adolescents with and without CD; and (ii) the association between HRV and grey matter brain volumes in key areas of the central autonomic network which are involved in self-regulation processes, such as insula, lateral/medial prefrontal cortices or amygdala. Respiratory sinus arrhythmia (RSA) measures of HRV were collected from adolescents aged between 9-18 years (693 CD (427F)/753 typically developing youth (TD) (500F)), as part of a European multi-site project (FemNAT-CD). The Inverse Efficiency Score, a speed-accuracy trade-off measure, was calculated to assess emotion and cognitive regulation abilities during an Emotional Go/NoGo task. The association between RSA and task performance was tested using multilevel regression models. T1-weighted structural MRI data were included for a subset of 577 participants (257 CD (125F); 320 TD (186F)). The CerebroMatic toolbox was used to create customised Tissue Probability Maps and DARTEL templates, and CAT12 to segment brain images, followed by a 2x2 (sex x group) full factorial ANOVA with RSA as regressor of interest. There were no significant associations between RSA and task performance, neither during emotion regulation nor during cognitive regulation trials. RSA was however positively correlated with regional grey matter volume in the left insula (p FWE=0.011) across all subjects. RSA was related to increased grey matter volume in the left insula across all subjects. Our results thus suggest that low RSA at rest might be a contributing or predisposing factor for potential self-regulation difficulties. Given the insula’s role in both emotional and cognitive regulation processes, these brain structural differences might impact either of those.